COLLABORATIVE GOVERNANCE DALAM MENINGKATKAN PRESTASI ATLET TENIS LAPANGAN DI KABUPATEN BANGKA - Akbar, M Rizki; Fikri, Zakiyudin (Universitas Panca Marga, 2023)
Field Tennis is one of the many sports in Bangka Regency. Has a fairly good achievement, but has problems experienced by athletes. This research method is descriptive qualitative, there are two types of data sources used in this study, namely primary and secondary. The results of this study are 1) Face-to-Face where there is a direct meeting to discuss a problem individually or in groups, 2) Build mutual trust between stakeholders, 3) Commitment to the Process of suggestions and joint achievement of results must be agreed upon, 4) Mutual understanding understanding between one institution or organization and another, 5) Interim Results Starting from a small victory is defined as what has been achieved by the collaborating parties. Recommendations from the author are: 1) To KONI and DISPORA of Bangka Regency as the venue for all sports in Bangka Regency to pay more attention to all the activities of athletes in Bangka Regency. 2) To Coaches and Parents of Athletes, so that in the future they will have a lot of connections or information in any field. 3) Setia Budi Sungailiat SMAS School, to search for students who excel in sports, so that they can create scholarship pathways, categories of students who have talent or achievements.